2014
DOI: 10.1080/02699931.2014.890563
|View full text |Cite
|
Sign up to set email alerts
|

Motivated empathy: The mechanics of the empathic gaze

Abstract: Successful human social interactions frequently rely on appropriate interpersonal empathy and eye contact. Here, we report a previously unseen relationship between trait empathy and eye-gaze patterns to affective facial features in video-based stimuli. Fifty-nine healthy adult participants had their eyes tracked while watching a three-minute long "sad" and "emotionally neutral" video. The video stimuli portrayed the head and shoulders of the same actor recounting a fictional personal event. Analyses revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 24 publications
16
57
0
Order By: Relevance
“…Together these results suggest that females seem to use global processing by default and therefore are not as affected by happy mood primes, while males do not use global processing by default and are therefore more sensitive to the happy prime. In related work, females fixated more on the eye regions of faces, compared to males, which may also be related to the female advantage in facial expression recognition (Hall et al, 2010), and which appears positively associated with empathetic skill (Cowan et al, 2014). …”
Section: Behavioral and Psychological Gender Differences In Humansmentioning
confidence: 92%
“…Together these results suggest that females seem to use global processing by default and therefore are not as affected by happy mood primes, while males do not use global processing by default and are therefore more sensitive to the happy prime. In related work, females fixated more on the eye regions of faces, compared to males, which may also be related to the female advantage in facial expression recognition (Hall et al, 2010), and which appears positively associated with empathetic skill (Cowan et al, 2014). …”
Section: Behavioral and Psychological Gender Differences In Humansmentioning
confidence: 92%
“…Regarding the process of facial emotional recognition, it has been suggested that it is related with a specific visual scan pattern, in which those who look at the eyes for a longer period of time show greater accuracy and speed to recognize emotions than those who spent less time looking on eyes' area (Hall and Masumoto, 2004;Calvo et al, 2008;Balconi and Canavesio, 2014). Some studies have reported participants spent more time looking at the eyes area in emotionally stimulus than neutral, highlighting the notion that eye-to-eye encounters are critical to successful engage social interactions (Mason et al, 2005;Cowan et al, 2014). In addition, some clinical abnormalities in socially directed eye-gaze patterns to facial features exhibit low-emotional empathy, such as schizophrenia, or autism (Klin et al, 2002;Joshua and Rossell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some clinical abnormalities in socially directed eye-gaze patterns to facial features exhibit low-emotional empathy, such as schizophrenia, or autism (Klin et al, 2002;Joshua and Rossell, 2009). In this context, it has been reported that empathy traits and gender can influence the visual scanning linked to emotional recognition (Balconi and Canavesio, 2014;Cowan et al, 2014;van Rijn et al, 2014). Otherwise, empathy traits have been described as the qualities or the empathic tendencies that people identify in themselves (Hoffman, 1977;Davis, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations